Conciliação, mediação e arbitragem no Brasil neoliberal: as associações patronais e suas instituições mediadoras (1994-2012) - Lance, Kleyne Paula Castro (2014)
In this work, our aim is to analysis the inter-relation with the institute/organs of mediation and arbitration founded by patronal institutions, showing up the movement that those settle in their midst, as well as, with the public sector. For both, we problematized the politics of reconciliation in the implementation process of Labor Legislation and then, the emergence of laws that have been implemented from this politics in the Brazilian legal scenario. In agreement, we find an infinite of private institutions which have struggled to regulate the Extra-judicial Methods of Dispute Settlement (MESCs) from the spread of Alternative Dispute of Resolution. So, this study narrowed its analysis with the mediation institutions, organs that are directly linked with a fraction of the industrial sector, therefore from the movement of these private apparatus of hegemony was constituted shape and contour to the Extended State from the their activities. Then, we have a hand in defense alternative forms of conflict resolution in court or privately and the other hand the traditional form of conflict resolution . Ultimately, two major projects were identified that are in dispute and that alternative forms have been gaining more space, as well as, they have been disputing this space in civil society, by role of employers and political society, by shareholder of the memberships and /or organic intellectuals